PECULIARITIES OF MODELING TECHNIQUE TEACHING - Ostapenko, Svitlana; Udovichenko, Hannah (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Based on a thorough analysis of psychological and pedagogical literature, main principles of didactics and cognitive psychology, through the prism of the works of prominent scientists of various years, modeling is considered as a powerful means of cognition which is used, as a rule, as an effective technique and teaching tool. The purpose of the article is to demonstrate the confirmation of the hypothesis that, when directive teaching the modeling method, the structure of the student’s mental activity changes, directive learning leads to improving the overall success of higher learning, and this can be expected to have a significant impact on future practical activities of an engineer. The analysis is carried out and the features of usage and advantages of application of the modeling method as a method of physics teaching are determined. It was justified that the use of the modeling method in teaching students of technical specialties offers the possibility to develop professionally significant skills, including the methodological knowledge of modeling that is so important for a modern specialist. There were used the following methods to solve the desired goal: the analysis of the scientific works regarding the matters under the inquiry; generalization of the own pedagogical experience, questioning, observation and generalization, mathematical processing of the obtained statistics.